Strengthening Student Character Based on Sufism Values: An Insight into Ethical Leadership Practices. - et al., Badrudin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main purpose of this paper is to focus on school principals’ perceptions of how they understand ethical leadership and make students have a commendable character based on Sufism values through the implementation of ethical leadership. The research method used was quasi-qualitative. This study utilizes semi-structured interviews with two private school principals to explore their perceptions of ethical leadership practices and nurture their students' commendable character based on Sufism values. There were two main findings. First, the commendable character based on the values of Sufism aims to achieve the pleasure of Allah, the Almighty God. Second, the effectiveness of the propagation from habit to belief is accelerated by ethical leadership behavior with the character of moral courage, humility, empathy, honesty, and self-control.